Progress in cancer mortality, incidence, and survival: a global overview - Santucci, Claudia; Carioli, Greta; Bertuccio, Paola; Malvezzi, Matteo; Pastorino, Ugo; Boffetta, Paolo; Negri, Eva; Bosetti, Cristina; La Vecchia, Carlo (European journal of cancer prevention, 2020)
Cancer mortality has declined over the last three decades in most high-income countries reflecting improvements in cancer prevention, diagnosis, and management. However, there are persisting and substantial differences in mortality, incidence, and survival worldwide. In order to provide an up-to-date overview of trends in mortality, incidence, and survival, we retrieved data from high-quality, population-based cancer registries for all cancers and 10 selected cancer sites in six high-income countries and the European Union. We computed age-standardized (world standard population) mortality and incidence rates, and applied joinpoint regression models. Mortality from all cancers and most common cancer sites has declined over the last 25 years, except for the pancreas and lung (in women). The patterns for incidence are less consistent between countries, except for a steady decrease in stomach cancer in both sexes and lung cancer in men. Survival for all cancers and the selected cancer sites increased in all countries, even if there is still a substantial variability. Although overall cancer death rates continue to decline, incidence rates have been levelling off among men and have been moderately increasing among women. These trends reflect changes in cancer risk factors, screening test use, diagnostic practices, and treatment advances. Many cancers can be prevented or treated effectively if they are diagnosed early. Population-based cancer incidence and mortality data can be used to focus efforts to decrease the cancer burden and regularly monitor progress towards cancer control goals.